2023
DOI: 10.1002/fsn3.3538
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the oral‐gut microbiota during thyroid cancer: Factors affecting the thyroid functions and cancer development

Yao Kun,
Wei Xiaodong,
Wang Haijun
et al.

Abstract: Thyroid cancer (TC) is categorized into papillary, follicular, medullary, and anaplastic. The TC is increasing in several countries, including China, the United States, the United Kingdom, Canada, France, Australia, Germany, Japan, Spain, and Italy. Thus, this review comprehensively covers the factors that affect thyroid gland function, TC types, risk factors, and symptoms. Lifestyle factors (such as nutrient consumption and smoking) and pollutants (such as chemicals and heavy metals) increased the thyroid‐sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 163 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Existing research suggests that the thyroid is closely linked to gut flora (Kun et al., 2023 ). In our study, we found that the prevalence of SIBO increased significantly after having hypothyroidism in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research suggests that the thyroid is closely linked to gut flora (Kun et al., 2023 ). In our study, we found that the prevalence of SIBO increased significantly after having hypothyroidism in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that FT4 was significantly lower and CRP was significantly higher in the group with hypothyroidism in pregnancy combined with SIBO compared to the group without SIBO, suggesting that the mechanisms associated between hypothyroidism in early pregnancy and SIBO may involve alterations in small intestinal bacteria, inflammatory factors, etc. On the one hand, hypothyroidism‐induced alterations in intestinal function relocate intestinal bacteria in the small intestine (Kun et al., 2023 ). Our findings support this reasoning: as expected, FT4 levels are negatively correlated with SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a relationship between thyroid cancer and the microbiota. Research on the relationship between oral bacteria has reported that an increase in the genera Alloprevotella , Anaeroglobus , and Acinetobacter , unclassified Bacteroidales , and unclassified Cyanobacteriales was observed in the saliva of patients with thyroid cancer [ 175 , 176 ]. Moreover, studies exist on the relationship between gut microbiota and thyroid cancer.…”
Section: Treatment Of Atcmentioning
confidence: 99%
“…resident in the human body, plays a vital role in both the maintenance of normal physiology and the occurrence of clinical outcomes [27,28]. The gut microbiota consists of almost 1200 bacterial species (at least 160 such species in each individual) and around 90% of the total human cells, whose gene count exceeds the human genome's gene count by ~100-fold [13,29,30]. The community of gut bacteria, most of which are strictly anaerobic and represent a mass of approximately 1.5-2 kg, is mainly composed (>90%) of Bacteroidetes, Firmicutes, Actinobacteria, Proteobacteria, and Verrucomicrobia, with Firmicutes and Bacteroidetes accounting for almost 90% of the population of the total gut microbiota [19,31,32].…”
Section: The Microbiota and Thyroid Axismentioning
confidence: 99%
“…Although more than 95% of TC cases belong to differentiated TC (PTC, FTC, and Hürthlecell carcinoma), deriving from thyroid follicular epithelial cells and characterized by an excellent prognosis [8,9], the etiology of TC is not fully clarified [10]. While childhood exposure to ionizing radiation, a history of benign thyroid nodules and goiter, and a family history of proliferative thyroid disease are established risk factors for TC, the role of other modifiable factors, such as dietary patterns and microbiota composition in TC carcinogenesis, have been recently explored [2,[11][12][13]. Deficiency of iodine, considered a trace element essential for the formation of thyroid hormones, has been associated with an increased risk of TC, promoting the development of FTC and ATC, while the effect of iodine supplementation, though still controversial, may influence the ratio of PTC to FTC, suggesting that an excessive iodine intake could act as a risk factor for PTC [11,14].…”
Section: Introductionmentioning
confidence: 99%